The assessment of fatigue: Psychometric qualities and norms for the Checklist individual strength - Worm-Smeitink, M.; Gielissen, M.; Bloot, L.; van Laarhoven, H.W.M.; van Engelen, B.G.M.; van Riel, P.; Bleijenberg, G.; Nikolaus, S.; Knoop, H. (Journal of psychosomatic research, 2017)
The Checklist Individual Strength (CIS) measures four dimensions of fatigue: Fatigue severity, concentration problems, reduced motivation and activity. On the fatigue severity subscale, a cut-off score of 35 is used. This study 1) investigated the psychometric qualities of the CIS; 2) validated the cut-off score for severe fatigue and 3) provided norms. Representatives of the Dutch general population (n=2288) completed the CIS. The factor structure was investigated using an exploratory factor analysis. Internal consistency and test-retest reliability were determined. Concurrent validity was assessed in two additional samples by correlating the CIS with other fatigue scales (Chalder Fatigue Questionnaire, MOS Short form-36 Vitality subscale, EORTC QLQ-C30 fatigue subscale). To validate the fatigue severity cut-off score, a Receiver Operating Characteristics analysis was performed with patients referred to a chronic fatigue treatment centre (n=5243) and a healthy group (n=1906). Norm scores for CIS subscales were calculated for the general population, patients with chronic fatigue syndrome (CFS; n=1407) and eight groups with other medical conditions (n=1411). The original four-factor structure of the CIS was replicated. Internal consistency (α=0.84–0.95) and test-retest reliability (r=0.74–0.86) of the subscales were high. Correlations with other fatigue scales were moderate to high. The 35 points cut-off score for severe fatigue is appropriate, but, given the 17% false positive rate, should be adjusted to 40 for research in CFS. The CIS is a valid and reliable tool for the assessment of fatigue, with a validated cut-off score for severe fatigue that can be used in clinical practice. •The Checklist Individual Strength (CIS), an instrument used to assess fatigue, is a reliable and valid measure of fatigue.•Cut-off scores for severe fatigue are presented that can be used in clinical practice and research.•Norms of CIS scores for the general population and eight different medical condition are presented.